SENTRALISME DAN PERLAWANAN DAERAH: DIALEKTIKA PERJALANAN SEJARAH BANGSA PASKAKOLONIAL (1945-2005) - Zed, Mestika (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
So that in the nature of man, we find three principal causes of quarrel. First, competition; secondly, diffidence; thirdly, glory. The first, make at men invade for gain; the second, for safety, and the third, for reputation. The first use violence, to make themselves masters of other men’s persons, wives, children, and cattle; the second, to defend them; the third, for trifle as a word, a smile, a different opinion, and any other sign of under value, either defect in their persons, or by reflection in their kindred, their friends, their nation, their profession, or their name. Thomas Hobbes, Leviathan, 1651. Key Words: Centralism, regional resistance, nation’s history.